Development of Mobile Network Monitoring System Fast Responsive Action On Network And System (mFRANS) - Pratomo, Istas; Affandi, Achmad; Riyanto, Dhany (JAVA Journal of Electrical and Electronics Engineering, 2014)
The increasing number of traffic on the network, due to the growth of smart devices such as gadgets and internet service at this time, causing high load of traffic. The network management is needed to find out the availability of the service, the network conditions, uptime and downtime. Simple Network Management Protocol (SNMP) is a protocol that is designed to monitor and set up a network based on TCP / IP either remotely or in a control center only. Through SNMP produce monitoring data in the form of raw data in the form of text, then the required application intermediaries to make the process monitoring be more efficient. This research will be to design, manufacture and testing the monitoring of all interfaces that exist on agent monitoring system that is more optimal. The experiment is conducted to determine the availability of devices and system using several methods, ie; on applications, network traffic and agent mapping, traffic in traffic out, polling system, urgent notification in the form text message and local alarm when detect the agent status up and down. The result of this study is a monitoring system that can provide a response notification to admin when there is agent down in the form text message with an average time of 22 to 30 seconds when the monitoring system detects the agent down and also traffic usage mapping, memory usage and availability.